Prediction of Location of Infarct-related Artery in acute Myocardial Infarction from Surface Electrocardiogram, its Clinical Importance and Therapeutic Strategy: A Review (University Heart Journal, 2015)
Abstract not availableUniversity Heart Journal Vol. 10, No. 2, July 2014; 85-87